Overseas Research. A Practical Guide - Barrett, Christopher B; Cason, Jeffrey W (Johns Hopkins University Press, 1997)
This guide is intended to give practical advice that prepares graduate student researchers for the realities and challenges of living and working abroad, with a particular focus on that area of research experience that is between participation and observation. Drawing on the experiences of 150 scholars, funded over a 6-year period by the MacArthur Scholars programs at Stanford University, the University of Wisconsin, and those supported by the Ford Foundation-funded Social Science Research Council's International Predissertation Fellowship Program, the book covers researchers experiences in 43 countries. The first chapters cover topics such as site selection, language training, project funding, and predeparture preparations. A chapter on living and working in the field covers issues of gender, race, class, and age, relations with expatriates, and settling in academically. Other chapters deal with issues such as the logistics of fieldwork (equipment/transportation/research assistants), dealing with sensitive subjects, selecting and cultivating information, and maintaining credibility. Knowing when and how to wrap up the research effort and go home is also discussed. The final chapters relate to general issues of organizing data, the writing process, getting reacclimated to home, and post-fieldwork obligations and opportunities. The text is expanded throughout by short, personal narratives. (Contains approximately 150 topically arranged bibliographic references.). (JLS)